Becoming who we are - "Rothbart, Mary K" (New York, 2011)
What are the basic dimensions of temperament? How does temperament influence children's relationships to their physical and social worlds--and their behavior and adjustment across the lifespan? What are its biological underpinnings? From preeminent researcher Mary Rothbart, this work comprehensively examines the role of temperament in the development of personality and psychopathology. In a direct and readable style, Rothbart combines theory and research with everyday observations and clinical examples. She offers new insights on difficult children and reviews intervention programs that address temperamental factors in childhood problems. Dr. Rothbart received the Eleanor Maccoby Book Award from Division 7 (Developmental Psychology) of the American Psychological Association for this book.
Keywords: Temprament in children